Regulation of RLR-Mediated Antiviral Responses of Human Dendritic Cells by mTOR - Fekete, Tünde; Ágics, Beatrix; Bencze, Dóra; Bene, Krisztián; Szántó, Antónia; Tarr, Tünde; Veréb, Zoltán; Bácsi, Attila; Pázmándi, Kitti (Frontiers in Immunology, 2020)
To detect replicating viruses, dendritic cells (DCs) utilize cytoplasmic retinoic acid inducible gene-(RIG) I-like receptors (RLRs), which play an essential role in the subsequent activation of antiviral immune responses. In this study, we aimed to explore the role of the mammalian target of rapamycin (mTOR) in the regulation of RLR-triggered effector functions of human monocyte-derived DCs (moDCs) and plasmacytoid DCs (pDCs). Our results show that RLR stimulation increased the phosphorylation of the mTOR complex (mTORC) 1 and mTORC2 downstream targets p70S6 kinase and Akt, respectively, and this process was prevented by the mTORC1 inhibitor rapamycin as well as the dual mTORC1/C2 kinase inhibitor AZD8055 in both DC subtypes. Furthermore, inhibition of mTOR in moDCs impaired the RLR stimulation-triggered glycolytic switch, which was reflected by the inhibition of lactate production and downregulation of key glycolytic genes. Blockade of mTOR diminished the ability of RLR-stimulated moDCs and pDCs to secret type I interferons (IFNs) and pro-inflammatory cytokines, while it did not affect the phenotype of DCs. We also found that mTOR blockade decreased the phosphorylation of Tank-binding kinase 1 (TBK1), which mediates RLR-driven cytokine production. In addition, rapamycin abrogated the ability of both DC subtypes to promote the proliferation and differentiation of IFN-y and Granzyme B producing CD8+ T cells. Interestingly, AZD8055 was much weaker in its ability to decrease the T cell proliferation capacity of DCs and was unable to inhibit the DC-triggered production of IFN-y and Granyzme B by CD8+ T cells. Here we demonstrated for the first time that mTOR positively regulates the RLR-mediated antiviral activity of human DCs. Further, we show that only selective inhibition of mTORC1 but not dual mTORC1/C2 blockade suppresses effectively the T cell stimulatory capacity of DCs that should be considered in the development of new generation mTOR inhibitors and in the improvement of DC-based vaccines.